SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMA PGRI 1 KOTA BEKASI - Nani Agustina; Dony Oscar (Paradigma, 2015)
SMA PGRI 1 Kota Bekasi is one of the leading private school in the town of Bekasi this school making lots optioned by prospective students parents current because the school was quite advanced, but the academic data processing in this school are still not integrated. Academic system which is running still using Ms application. Excel, without the database. The result of these many obstacles faced by the school in academic administration as in data processing of teachers, student data, data subjects, lesson schedule, update the assessment, assessment reports, announcements, class settings, the settings of walikelas, contacts, school report cards and school year shadow. In addition, the presentation of information is still lacking a fast, precise and accurate delivery of information because the media is currently the only form of mading and selembaran such as physical paper documents announcement. In this Academic information system using the PHP programming language and Mysql as the database. In the current information systems have become the premier choice for giving and looking for information on a specific data, SMA PGRI 1 Kota Bekasi is one school which offers web-based information systems in managing academic data , making it easier for the schools to manage , inform and find the data related to academic at SMA PGRI 1 Kota Bekasi. Keywords: Information Systems, Web-Based Admission, Waterfall, UML